Hybrid precoding and power allocation for mmWave NOMA systems based on time delay line arrays - Gangcan SUN; Xinli WU; Wanming HAO; Zhengyu ZHU (Tongxin xuebao)
Objectives: The antenna structure in conventional millimeter-wave (mmWave) nonorthogonal multiple access(NOMA)systems is based on a high-resolution and high-energy phase shifter modulation network,and how to reduce the system energy consumption while improving the resolution is one of the key problems to be solved. In this thesis, a lowcomplexity and low-power delay line array consisting of switches and delay lines for continuous phase modulation is introduced into the mmWave NOMA system, and the energy efficiency(EE)and spectral efficiency(SE)of the system are investigated. Methods:To reduce inter-user interference,an improved K-means algorithm is proposed to group users and select a cluster head for each group of users, which maximizes the correlation of user channels in the same cluster and reduces the correlation between users in different clusters as much as possible;Then,a low-complexity analog precoding is designed to maximize the array gain of the antenna based on the relevant user channel matrix composed of the cluster head set, followed by a digital precoding designed to eliminate inter-user interference with the maximum equivalent channel gain between beams using a forced-zero technique; Finally, an EE maximization problem is formed to optimize the transmit power under users'quality of services and total transmit power constraints,and a two-layer iterative algorithm is proposed for the resulting non-convex optimization problem. Specifically,the Dinkelbach method is applied in the outer layer to transform the fractional structure of the objective function in EE optimization into a subtractive structure, and the non-convex objective function is transformed into a convex function by using mathematical tools in the inner layer, and then an iterative algorithm based on alternating optimization (AO) is proposed for power allocation, and finally the solution of the initial problem is obtained by circular iteration in both inner and outer layers. Results:Simulation analysis:(1)The figure6(a)show that the SE of the proposed scheme is higher than that of the conventional phase-shifter modulation network with fully-connected and sub-connected hybrid precoding structures; In addition, the system SE of the fullconnected structure under the proposed scheme is better than that of the hybrid-connected and sub-connected structures.(2) the figure6(b) show that the EE of the system under the proposed scheme is also better than that of the conventional phase-shifter network-based and fully-digital precoding structures; Also, the system SE of the sub-connected structure under the proposed scheme is better than that of the hybrid-connected and fully-connected structures. (3) The figure7(a) show that the SE of the system increases as the number of antennas increases;The figure7(b)show that the EE of the system decreases as the number of antennas increases. (4) The figure8(a) and (b) show that compared with the mmWave orthogonal multiple access (OMA) system based on the time-delayed line array, and the proposed scheme can achieve better performance in terms of EE and SE.(5)the figure9(a) show that the performance of the proposed improved K-means user grouping algorithm is better than the K-means user grouping algorithm.Although the K-means can be done better based on the state information of the channel,the randomness of its initial cluster head will affect the convergence of the algorithm and the system performance. In addition, the random grouping algorithm has the worst performance because there is user interference in NOMA system,and the random grouping will make the user interference in the same cluster increase. Conclusions: The time-delay line array is composed of low-power, low-complexity switches and delay lines,and the continuous phase modulation can be realized by adjusting the switches.The proposed mmWave NOMA system based on delay line array constructed can effectively improve the SE and EE of the system.